Factors that affect the proliferation of direct-selling business in Iloilo City - Amarillo, Marites; Bolivar, Suzette; Borra, Leandro; Claridad, Marianne Amour; Mirasol, Kareen
The study was conducted to find out the factors that encourage the Proliferation of Direct-Selling Business in Iloilo City. The main source for acquiring the information are the questionnaires. Two sets of questionnaires were distributed: one for management group and another one for customer group. In the management group, companies selected were divided into four categories namely: a) Cosmetics, b) Intimate Apparel, c) Clothes/Garments and d) Food supplement. At least three must fall under each category. The manager or his authorized representative must be able to answer the questionnaires prepared for each company. For the customer group, sixty people were randomly picked to answer the questionnaires, among which, only forty responded. Results of the study showed that some of the most relevant factors that affect the proliferation of direct-selling business are profitability, marketing strategies employed by the companies, good motivation of its sales force, and the ease to get involved and succeed in the said venture.